2011
DOI: 10.1063/1.3553643
|View full text |Cite
|
Sign up to set email alerts
|

Mesocopic comparison of complex networks based on periodic orbits

Abstract: Complex noiseless dynamical systems can be represented in a compressed manner by unstable periodic orbits. It is unknown, however, how to use this technique to obtain a suitable notion of similarity among them, how to extend such an approach to more general complex networks, and how to apply such a method in the important case of noisy systems. Our approach provides a solution to these questions. For a proof-of-concept, we consider Drosophila's precopulatory courtship, where our method reveals the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Power-law like bursts of cortical activity were also observed on a more macroscopic scale in sleep experiments [13,14]. The issue of functional relevance is avoided in this paper by working instead with functional output itself: the body language actions of Drosophila melanogaster during its pre-copulatory courtship [15,16] provides an opportunity to code and study distinct, relevant, neural states, in terms of a clearly defined and finite set of fundamental actions. Sequences of these fundamental actions naturally define a network, which gives a glimpse of the topology of transitions between relevant neural states expressable by the system.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Power-law like bursts of cortical activity were also observed on a more macroscopic scale in sleep experiments [13,14]. The issue of functional relevance is avoided in this paper by working instead with functional output itself: the body language actions of Drosophila melanogaster during its pre-copulatory courtship [15,16] provides an opportunity to code and study distinct, relevant, neural states, in terms of a clearly defined and finite set of fundamental actions. Sequences of these fundamental actions naturally define a network, which gives a glimpse of the topology of transitions between relevant neural states expressable by the system.…”
Section: Introductionmentioning
confidence: 84%
“…In this paper, the sequence types are studied in 3 groups: male behaviour ; female behaviour ; and male and female behaviour ( Table 1). We use behaviour in the sense defined in [15,16], so that the female behaviour includes the gender switching observed in male vs. fruitless (however sequences produced by fruitless as protagonist are excluded).…”
Section: Network Underlying Drosophila Pre-copulatory Courtship (Dpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Behavior is characterized by rituals that consist of well-chosen sequences of individual actions. Since it is in the nature of these rituals that they need to be repeated if required, we characterize behavior by sequences of indecomposable closed cycles of indecomposable individual actions, so-called irreducible cycles of irreducible acts [11], [12]. This approach is also motivated by the theory of complex dynamical systems, where it has been shown that such systems can be reduced to a minimal set of closed sequences of actions (there called ‘irreducible closed orbits’).…”
Section: Introductionmentioning
confidence: 99%
“…Using a decomposition of courtship data into irreducible cycles, it has been found that with high confidence during D. ’s precopulatory courtship, individual information is transmitted to the prospective partner, i.e. genuine communication with essential information exchange takes place [11], [12] (Fig. S2).…”
Section: Introductionmentioning
confidence: 99%